María del Carmen Huerta or a denial of social identity in ¡Qué viva la música! - Carvajal, Edwin Alberto (Íkala, Revista de Lenguaje y Cultura, 1998)
The author of this article relates the development of the protagonist - Maria del Carmen Huerta as well called Siempreviva - identity through the emerging musical genre, the salsa. He shows how the salsa in the seventies in Cali. as opposed to rock and traditional Colombian music, becomes for A. Caicedo the essencial element of her fragmented identity.